Efflorescence during the drying of a technical gypsum body: Application of thermodynamic principles. (11th October 2021) - Fobbe, N.; Goetz-Neunhoeffer, F.; Foerster, H.; Foerthner, S.; Jansen, D.
Highlights: The drying process of a gypsum plaster was investigated. The growth of Mg-sulfate efflorescence on gypsum plaster is hindered by OPC addition. It was shown, that with OPC addition, other Mg-phases potentially can form. Thereby, the Mg depletion prevents Mg-sulfate precipitation. Abstract: The drying process of a technical flue gas desulphurization (FGD) gypsum body was studied. At low surface-to-volume ratios, it showed a significant efflorescence of hexahydrite (MgSO4 ·6H2 O) after less than one day. A countermeasure against this phenomenon is the addition of small amounts of Ordinary Portland Cement (OPC) (0.2 wt%). Prisms of pure FGD and FGD-OPC mixtures were synthesized and investigated with a combination of 1 H-TD-NMR and ICPMS measurements to monitor both the physical water content during the drying process and the chemical pore water composition within the first 48 h. The experiments showed no differences in the drying rate and pore water distribution and only small differences in the pore water composition. In combination with thermodynamic calculations, the prevention of efflorescence could be attributed to chemical processes in the pore water. Mg-sulfates potentially can form on both samples with the same chance. Therefore, it was concluded that OPC can only hinder efflorescence indirectly by decreasing the Mg concentration in the pore water. An increase in pH can cause Mg-phases to precipitate, thereby binding the Mg before Mg-sulfates can form on the surface of the body. Further calculations revealed, that the two phases hydrotalcite and M−S−H can potentially form inside the FGD-OPC prism, probably due to an increase of the pH.